2014
DOI: 10.1021/nl500862u
|View full text |Cite
|
Sign up to set email alerts
|

New Insight in Understanding Oxygen Reduction and Evolution in Solid-State Lithium–Oxygen Batteries Using an in Situ Environmental Scanning Electron Microscope

Abstract: Via designing a facile microscale all-solid-state lithium-oxygen battery system constructed in an environmental scanning electron microscope, direct visualization of discharge and charge processes of the lithium-oxygen battery is achieved. Different morphologies of the discharge product are observed, including a sphere, conformal film, and red-blood-cell-like shape, with a particle size up to 1.5 μm; whereas upon charge, the decomposition initiates at their surface and continues along a certain direction, inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
120
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(134 citation statements)
references
References 38 publications
8
120
3
Order By: Relevance
“…4F and 1C). This observation of the morphology of the discharge products and its growth pattern in accordance with the discharge/charge cycle was consistent with others [17,27,55,56]. The average size of the discharge products during discharge and charge are summarized in Table S2 within the Supporting Information.…”
Section: Resultssupporting
confidence: 89%
“…4F and 1C). This observation of the morphology of the discharge products and its growth pattern in accordance with the discharge/charge cycle was consistent with others [17,27,55,56]. The average size of the discharge products during discharge and charge are summarized in Table S2 within the Supporting Information.…”
Section: Resultssupporting
confidence: 89%
“…Similarly, Zheng et al constructed an SSLAB that consisted of super-aligned CNT (SACNT), native Li 2 O layer electrolyte, and Li anode in an environmental SEM. [115] Their results showed that some discharge products with sizes ranging from 500 nm to 1 µm preferred to grow on CNT-SE-oxygen three-phase interface, while smaller discharge products tended to grow along the CNT. The SEM images in Figure 8 clearly stated that the Li 2 O 2 particle grew on the solid electrolyte-CNT-oxygen triple phase interface during discharge and that the electronic and ionic conductivities of Li 2 O 2 could support this growth.…”
Section: Reaction Mechanism In the Solid-state Li-air (O 2 ) And Li-smentioning
confidence: 98%
“…Reprinted with permission from Ref. [32]. Copyright (2014) American Chemical Society The gray shaded region indicates the target conductivity needed to meet performance requirements, as discussed in the text; b proposed two-stage recharge mechanism for a Li-air cell.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with that of Gerbig et al [33], who experimentally proved that the electronic conduction (*10 -12 S/cm) of bulk Li 2 O 2 was less than its ionic conductivity (*10 -10 S/cm). But Zheng et al [32] drew a different conclusion based on an in situ environmental scanning electron microscope (SEM) of a solid-state Li-O 2 battery. They argued that the oxidation process initiated at the surface of Li 2 O 2 , not at the electrode/Li 2 O 2 or electrolyte/Li 2 O 2 interface (Fig.…”
Section: Initial Oxidation Locationmentioning
confidence: 99%
See 1 more Smart Citation